The Using of Tenses In English Translation of Surah Al-Mulk - Dewi, Shoufi Nisma; Grahmayanuri, Novria; Iqbal, Muhammad (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstractThis study discusses about the using of tenses in English Translation of Surah Al-Mulk translated by Dr. Mustafa Khattab. This research is conducted by qualitative data analysis. The data of this study are clauses that contained tenses which are found in English Translation of Surah Al-Mulk translated by Dr. Mustafa Khattab. The source of data in this study is website addressed https://quran.com/al-mulk. The data are collected by using documentary technique, particularly in content analysis. The data are transcribed into clauses and analyzed through the using of tenses. In analyzing the data, the researcher applied interactive model of Miles, Huberman and Saldana (2014:33). The findings of the study found the using of tense in English Translation of Surah Al-Mulk, they are involved Simple Present is the higher result which reaches 56 %, simple future tense occurs for 18 %, simple past tense occurs for 14%. The other supported tenses found are present perfect tense which almost occurs for 4 occurances or it has 4%, past future perfect is written for twice or 2 %, and past perfect tense is the lower result found in which occurs for merely once or 1 %. There are 6 clauses which do not apply the using of tenses since some are represented as expression, the using of modals, or the translator does not follow the formulation of any tense or in another words a mistaken form of tense.Keywords: Tenses, Translation, Al-Quran, Al-Mulk.